Evaluation of plant extracts for induction of defence against Fusarium wilt in chickpea - P.N. RAKHONDE and S.S. MANE, A.D. GAWANDE*, S. GANGOPADHYAY (Indian Phytopathology, 2015)
In the present investigations, effect of six plant parts extracts viz., leaf extracts of Calotropis procera, Eucalyptus globulus and Withania somnifera, fruit extract of Citrullus colocynthis and leaf and seed kernel extracts of Azadirachta indica was assayed on host defense triggery mechanism. The activities of soluble phenol, and protein contents, peroxidase, polyphenol oxidase, phenylalanine ammonia-lyase, Î²-1, 3-glucanase and chitinase activities in chickpea roots were observed. The effect of plant extracts on wilt incidence, seed germination and plant growth parameters viz., root and shoot lengths and dry weight in chickpea and the population of Fusarium oxysporum f. sp. ciceri in soil was also recorded under greenhouse condition. Seed treatment and soil application of aqueous extracts of A. indica seed kernel, C. colocynthis fruit and A. indica leaf significantly increased the soluble phenol, and protein contents and the activities of peroxidase, polyphenol oxidase, phenylalanine ammonia-lyase, Î²-1, 3-glucanase and chitinase activities in chickpea roots. Seed treatment and soil application of aqueous extracts of A. indica seed kernel, C. colocynthis fruit and A. indica leaf reduced the wilt incidence of Fusarium wilt, population of F. oxysporum f. sp. ciceri in soil and increased root and shoot lengths and dry weight of chickpea plants.